Exposure to mono (2‐ethylhexyl) phthalate facilitates apoptosis and pyroptosis of human endometrial microvascular endothelial cells through NLRP3 inflammasome. Issue 5 (7th November 2020) - An, Lijuan
Abstract: Mono (2‐ethylhexyl) phthalate (MEHP) is a major metabolite of di (2‐ethylhexyl) phthalate (DEHP). This study aimed to observe the toxic effect of MEHP on human endometrial microvascular endothelial cells (HEMECs) and its potential molecular mechanism. HEMECs were exposed to different concentrations of MEHP (0, 50, 100, and 200 nM). Cell viability and apoptosis were assessed by cell counting kit‐8 (CCK‐8) and flow cytometry assays. Western blot was performed to examine the expression of apoptosis‐related proteins (Bcl‐2, Bax, and Caspase‐3). Moreover, the expression of pyroptosis‐related Caspase‐1 was detected by western blot and immunofluorescence assays. Lactate dehydrogenase (LDH) release levels were evaluated in HEMECs treated with MEHP and/or Caspase‐1 inhibitor Ac‐YVAD‐CHO. After exposure to MEHP, NLRP3 expression was examined by reverse transcription quantitative polymerase chain reaction (RT‐qPCR) and western blot. LDH release and apoptosis levels were tested in HEMECs induced by MEHP and/or siNLRP3. MEHP significantly induced cell viability and inhibited apoptosis for HEMECs, with a concentration‐dependent manner. Furthermore, Bcl‐2/Bax ratio was distinctly reduced and Caspase‐3 expression was increased in HEMECs after exposure to MEHP. Western blot and immunofluorescence results confirmed that MEHP markedly augmented Caspase‐1 expression in HEMECs. Furthermore, LDH release levels were fortified in HEMECs treated with MEHP, which were improved following cotreatment with Ac‐YVAD‐CHO. At the mRNA and protein levels, NLRP3 expression was prominently increased in HEMECs exposed to MEHP. NLRP3 knockdown markedly ameliorated the increase in LDH release and apoptosis induced by MEHP exposure in HEMECs. Our findings suggested that exposure to MEHP facilitates apoptosis and pyroptosis of HEMECs through NLRP3 inflammasome. Abstract : Our study evaluated the toxic effect of MEHP on HEMECs and its underlying molecular mechanism. The results showed that MEHP significantly induced cell viability and suppressed apoptosis for HEMECs. LDH release was enhanced in HEMECs exposed to MEHP, improved by cotreatment with Ac‐YVAD‐CHO. NLRP3 expression was prominently increased following exposure to MEHP. NLRP3 knockdown ameliorated the increase in LDH release and apoptosis induced by MEHP exposure. Thus, our findings suggested that MEHP facilitates apoptosis and pyroptosis of HEMECs through NLRP3.